Factors associated with hospital mortality in renal transplant patients admitted to the intensive care unit with acute respiratory failure - Silva,Rafael Mendes da (2017)
Abstract Introduction: The lungs are often involved in a variety of complications after kidney transplantation. Acute respiratory failure (ARF) is one of the most serious manifestations of pulmonary involvement. Objective: To describe the main causes of ARF in kidney transplant patients who require intensive care and identify the factors associated with mortality. Methods: This retrospective study evaluated adult patients with ARF admitted to the intensive care unit of a center with high volume of transplants from August 2013 to August 2015. Demographic, clinical, and transplant characteristics were analyzed. Multivariate logistic regression analysis was performed to identify factors associated with hospital mortality. Results: 183 patients were included with age of 55.32 ± 13.56 years. 126 (68.8%) were deceased-donor transplant, and 37 (20.2%) patients had previous history of rejection. The ICU admission SAPS3 and SOFA score were 54.39 ± 10.32 and 4.81 ± 2.32, respectively. The main cause of hospitalization was community-acquired pneumonia (18.6%), followed by acute pulmonary edema (15.3%). Opportunistic infections were common: PCP (9.3%), tuberculosis (2.7%), and cytomegalovirus (2.2%). Factors associated with mortality were requirement for vasopressor (OD 8.13, CI 2.83 to 23.35, p < 0.001), invasive mechanical ventilation (OD 3.87, CI: 1.29 to 11.66, p = 0.016), and SAPS3 (OD 1.04, CI 1.0 to 1.08, p = 0.045). Conclusion: Bacterial pneumonia is the leading cause of ARF requiring intensive care, followed by acute pulmonary edema. Requirement for vasopressor, invasive mechanical ventilation and SAP3 were associated with hospital mortality.